Crisis communication in the area of risk management: the CriCoRM project - Carmelo Scarcella; Laura Antonelli; Grazia Orizio; Constanze Rossmann; Lena Ziegler; Lisa Meyer; Leonarda Garcia-Jimenez; Jose Carlos Losada; Joao Correia; Joana Soares; Loredana Covolo; Enrico Lirangi; et al. (SAGE Publishing, 2013)
Background. During the last H1N1 pandemic has emerged the importance of crisis communication as an essential part of health crisis management. The Project aims specifically to improve the understanding of crisis communication dynamics and effective tools and to allow public health institutions to communicate better with the public during health emergencies. Design and Methods. The Project will perform different activities: i) state of the art review; ii) identification of key stakeholders; iii) communicational analysis performed using data collected on stakeholder communication activities and their outcomes considering the lessons learnt from the analysis of the reasons for differing public reactions during pandemics; iv) improvement of the existing guidelines; v) development of Web 2.0 tools as web-platform and feed service and implementation of impact assessment algorithms; vi) organization of exercises and training on this issues. Expected impact of the study for public health. In the context of health security policies at an EU level, the project aims to find a common and innovative approach to health crisis communication that was displayed by differing reactions to the H1N1 pandemic policies. The focus on new social media tools aims to enhance the role of e-health, and the project aims to use these tools in the specific field of health institutions and citizens. The development of Web 2.0 tools for health crisis communication will allow an effective two-way exchange of information between public health institutions and citizens. An effective communication strategy will increase population compliance with public health recommendations.